Prospective Assessment of Life Cycle, Quality, and Cost for Electric Product Improvement: Supporting Prototyping and Conceptualization by Employing CQ-LCA - Dominika Siwiec; Andrzej Pacana (Energies, 2025)
The process of conceptualisation and prototyping of electric energy products is demanding due to the need for a multifaceted approach to product design. This task becomes even more complex during sustainable development, within which supporting techniques are sought. Energy conversion products such as electric motorcycles require special attention due to their impact on energy efficiency, environmental emissions, and operating and production costs. The research gap refers to the lack of a model to aggregate these aspects simultaneously. The objective of the research was to develop a CQ-LCA model (Cost–Quality–Life Cycle Assessment) supporting the creation of alternative product solutions and their evaluation in terms of the following: (i) environmental impact in the life cycle (LCA), (ii) quality, and (iii) production and/or purchase costs. The model was developed in seven main stages and tested for electric motorcycles and their ten prototypes, which are examples of modern products that convert electrical energy into mechanical energy. Using the EDAS method, the quality of electric motorcycle prototypes was calculated. Then, by the LCA method according to ISO 14040, the CO2 emissions were estimated and modelled adequately to quality change. Next, by the parametric model based on the static method and the cost value function, including the nominal least squares method, the cost was estimated adequately to quality and environmental change. The model provided a qualitative and quantitative interpretation of electric motorcycle prototypes (CQ-LCA), allowing for the consideration of product characteristics, such as engine power, charging time, and battery capacity, but also environmental impacts and costs. The originality is the provision of a multi-aspect morphological analysis, after which different scenarios of product solutions. The model can be useful for various commonly used energy-converting products.